Route knowledge and configural knowledge in typical and atypical development: a comparison of sparse and rich environments. Issue 1 (December 2015) - Farran, Emily; Purser, Harry; Courbois, Yannick; Ballé, Marine; Sockeel, Pascal; Mellier, Daniel; Blades, Mark
Abstract Background Individuals with Down syndrome (DS) and individuals with Williams syndrome (WS) have poor navigation skills, which impact their potential to become independent. Two aspects of navigation were investigated in these groups, using virtual environments (VE): route knowledge (the ability to learn the way from A to B by following a fixed sequence of turns) and configural knowledge (knowledge of the spatial relationships between places within an environment). Methods Typically developing (TD) children aged 5 to 11 years (N = 93), individuals with DS (N = 29) and individuals with WS (N = 20) were presented with a sparse and a rich VE grid maze. Within each maze, participants were asked to learn a route from A to B and a route from A to C before being asked to find a novel shortcut from B to C. Results Performance was broadly similar across sparse and rich mazes. The majority of participants were able to learn novel routes, with poorest performance in the DS group, but the ability to find a shortcut, our measure of configural knowledge, was limited for all three groups. That is, 59 % TD participants successfully found a shortcut, compared to 10 % participants with DS and 35 % participants with WS. Differences in the underlying mechanisms associated with route knowledge and configural knowledge and in the developmental trajectories of performance across groups were observed. Only the TD participants walked a shorter distance in the last shortcut trial compared to the first, indicative of increased configural knowledge across trials. The DS group often used an alternative strategy to get from B to C, summing the two taught routes together. Conclusions Our findings demonstrate impaired configural knowledge in DS and in WS, with the strongest deficit in DS. This suggests that these groups rely on a rigid route knowledge based method for navigating and as a result are likely to get lost easily. Route knowledge was also impaired in both DS and WS groups and was related to different underlying processes across all three groups. These are discussed with reference to limitations in attention and/or visuo-spatial processing in the atypical groups.